CHARACTERISTICS OF THE TRANSLATION OF MODERN IT TERMINOLOGY FROM ENGLISH INTO UZBEK - Anarkulova Go’zal Abdurashid qizi (TADQIQOTLAR, 2025)
Abstract: ICT terms are a relatively new field for the Uzbek language, which has  entered  the  Uzbek  lexicon  through  Russian  and  directly  through  English. Therefore,  most  ICT  terms  have  features  specific  to  English  lexicon.  It  has  been decades since the first computers were created, and the last generation of computers has been aroundfor a long time, during which time computer language has gone beyond the scope of professional use and into the everyday speech of language owners.